Discovering a Young State: Foreign Sports Delegations in the USSR during the 1920s - A. M. Glushich (Vestnik MGIMO-Universiteta)
In the 1920s, visits by foreign delegations to the USSR served as a crucial yet challenging avenue for showcasing the achievements of the nascent Soviet state. Drawing on previously unexplored materials from the Russian State Archive of Socio-Political History (F. 537, inv. 2), this article examines the strategies employed in hosting these guests. It explores the planning of their itineraries and leisure activities, aiming to understand how Soviet sports leaders, during the early stages of state formation, skillfully concealed various shortcomings (especially economic and infrastructural) and highlighted sports and cultural triumphs to craft a positive global image of the USSR through what was ostensibly a non-political institution.Soviet physical education leaders did not shy away from inviting foreign teams to the country; instead, they actively welcomed all interested parties who could manage the journey. An ideally orchestrated visit seamlessly integrated four key elements: sports (the competitions), culture (theater, cinema, sightseeing), daily life (direct interaction with Soviet workers), and team recreation. When executed well, these visits garnered positive international feedback, thereby enhancing the USSR's global prestige as the inaugural socialist state. This became the primary objective of Soviet sports diplomacy in the late 1920s, marking a significant stride in breaking through international isolation.However, these visits were not without limitations and challenges. The level of indoctrination varied significantly among delegations: while European proletarians often visited sites significant to the October Revolution, guests from the East were predominantly exposed to the country's cultural facets. Despite the Red Sports International's encouragement, delegations rarely ventured beyond major urban centers like Moscow, Leningrad, Kharkov, and Odessa, as provincial visits were not feasible. Furthermore, even in these key cities, visitors encountered organizational challenges such as transportation difficulties, inadequate economic support, and issues with food provision, which diminished the effectiveness of propaganda efforts. These shortcomings were largely attributable to the absence of a standardized protocol for receiving foreign guests during the first decade of Soviet sports diplomacy and the general uneven infrastructural development of the country.